2018
DOI: 10.1101/324202
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Active sensing with light improves predator detection in a diurnal fish

Abstract: 20Active sensing by means of light is rare. In vertebrates, it is known only from chemiluminescent fish 21 with light organs below their pupils, an anatomical arrangement that is ideal to generate eyeshine in 22 the pupils of nearby organisms. Here, we test whether diurnal fish can achieve the same by 23 redirecting sunlight through reflection instead. We recently showed that small (< 5 cm), benthic, 24 marine triplefin fish actively redirect downwelling light using their iris. We hypothesized that this 25 mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
(1 reference statement)
0
1
0
Order By: Relevance
“…The majority of fish, including Percidae, have a reflective layer behind the photoreceptors of the retina, the retinal tapetum lucidum, and, as a result, their eyes show reflectance in the water [37,38]. Such reflection has been shown to increase predation risk [39]. In addition, studies have shown that fish predators attack at eye region of the fish or eye spot on the body [40].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of fish, including Percidae, have a reflective layer behind the photoreceptors of the retina, the retinal tapetum lucidum, and, as a result, their eyes show reflectance in the water [37,38]. Such reflection has been shown to increase predation risk [39]. In addition, studies have shown that fish predators attack at eye region of the fish or eye spot on the body [40].…”
Section: Discussionmentioning
confidence: 99%